Graphite and preparation method thereof, anode slurry, negative electrode sheet, battery and electrical equipment

Through the graphite prepared by needle coke, the oil absorption value and the particle size ratio are controlled, and the cost increase and dispersion problems caused by excessive graphite oil absorption value in the prior art are solved, thereby achieving more efficient battery performance.

CN115939377BActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211343628.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2025-02-25
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the excessive oil absorption value of graphite leads to consumption of more dispersant and binder when preparing the anode slurry, which increases costs. At the same time, the low oil absorption value will lead to poor dispersion.

Method used

Graphite is prepared by needle coke, and its oil absorption value is controlled within the range of 45-65 cm3/100g. By optimizing the particle size ratio and the use of cladding materials, the graphitization degree and tap density of graphite are improved.

Benefits of technology

The consumption of dispersant and binder during the preparation of the anode slurry is reduced, and the cost is reduced. At the same time, the electrolyte infiltration performance of the negative electrode sheet and the fast charging and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115939377B_ABST
    Figure CN115939377B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and in particular to a graphite and a preparation method thereof, an anode slurry, a cathode electrode sheet, a battery and an electrical device. The graphite provided in the present application is prepared from needle coke, and the oil absorption value DBP of the graphite is 45-65, in units of cm 3 / 100g. Due to the high oil absorption value of graphite, more dispersant and binder will be consumed in the process of preparing anode slurry, increasing the cost. The oil absorption value of this application is 45cm 3 / 100g‑65cm 3 / 100g, indicating that the exposed end face of the graphite is reduced. In the process of using the graphite as the negative electrode material to prepare the slurry, the consumption of dispersant and binder is reduced, which can reduce the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to graphite and a preparation method thereof, anode slurry, negative electrode sheet, battery and electrical equipment. Background Art

[0002] In lithium-ion batteries, the current mainstream negative electrode material is still graphite-based negative electrode material, which has a lower lithium insertion potential during the reaction process. At the same time, the generated lithium intercalation intercalation compound replaces the metallic lithium negative electrode, thereby avoiding the deposition of metallic lithium dendrites, and thus significantly improving safety.

[0003] Oil absorption value is DBP value, unit is cm 3 / 100g. Under the specified test conditions, the volume (cm2) of dibutyl phthalate (DBP, di-n-butyl phthalate) absorbed by 100g of material 3 ) number. It is generally used to characterize the degree of aggregation of material particles. Graphite has a large oil absorption value, and more dispersants and binders will be consumed in the process of preparing anode slurry, increasing costs. Summary of the invention

[0004] The main purpose of the present invention is to provide a graphite, which is used as a negative electrode material to reduce costs.

[0005] To achieve the above object, the present invention provides a graphite, wherein the graphite is prepared from needle coke, and the oil absorption value DBP of the graphite ranges from 45 to 65, in units of cm 3 / 100g.

[0006] Optionally, the DBP of the graphite is in the range of 50-53, in cm 3 / 100g.

[0007] In the process of preparing anode slurry, if the oil absorption value of graphite is too high, it will lead to more consumption of dispersant and binder, and increase the cost. However, if the oil absorption value of graphite is too low, it will lead to poor dispersibility when the amount of binder is small. Therefore, the oil absorption value should not be too high or too low. The DBP of graphite can be 50cm 3 / 100g、51cm 3 / 100g、52cm 3 / 100g、53cm 3 / 100g, not specifically limited.

[0008] Optionally, the graphitization degree G of the graphite is greater than 94%.

[0009] The graphite in this application has a graphitization degree G greater than 94%. The higher the graphitization degree G, the more regular the carbon material structure and the larger the specific surface area. When the graphite is used in the negative electrode plate, the electrolyte wetting performance of the negative electrode plate can be improved, the lithium ion transmission path can be shortened during the charge and discharge process, and the fast charge and cycle performance of the battery can be improved. The graphitization degree G can be 94.1%, 95%, 96%, 97%, 98%, 99%, 100%, and there is no specific limitation.

[0010] Optionally, the BET specific surface area of ​​the graphite is in the range of 0.9-1.5, in m 2 / g.

[0011] The large specific surface area means that graphite can accommodate more lithium ions, which is beneficial to increase the battery capacity. The specific surface area of ​​graphite BET can be 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 14m 2 / g, 1.5m 2 / g, no specific limit.

[0012] Optionally, the BET value of the graphite is in the range of 1.2-1.4, in m 2 / g.

[0013] It is understandable that a low specific surface area will result in a low oil absorption value. In order to obtain an appropriate range of oil absorption values, the value range of the specific surface area cannot be too large. The BET of graphite can be 1.2 m 2 / g, 1.3m 2 / g, 1.4m 2 / g, no specific limit.

[0014] Optionally, the tap density TD of the graphite is in the range of 0.9-1.4, in g / cm 3 .

[0015] The high tap density indicates that in the process of applying graphite to the negative electrode, a thinner active material layer can be prepared, so that more lithium ions can be stored in the same volume, thereby improving the energy density. The tap density TD of graphite can be 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3It is understood that the tap density is affected by the particle size of the material, and when the average particle size Dv50 of graphite is in the range of 10 μm-20 μm, the tap density TD in the above range can be obtained.

[0016] Optionally, the TD of the graphite is in the range of 1.0-1.1, in g / cm 3 .

[0017] The tap density cannot be too large. If the tap density is too large, lithium ions are not easily embedded, which deteriorates fast charging. It is understandable that a large tap density reduces the number of pores, which is not conducive to electrolyte infiltration, and lithium ions cannot be transmitted in time, thus deteriorating fast charging. Therefore, the TD of graphite can be 1.0g / cm 3 or 1.1 g / cm 3 It is understood that the tap density is affected by the particle size of the material, and the Dv50 of graphite is in the range of 14 μm-16 μm, and the tap density TD in the above range can be obtained.

[0018] Optionally, the discharge capacity Cap of the graphite is in the range of 340-360, in units of mA·h / g.

[0019] The graphite of the present application can satisfy the range value of the discharge capacity Cap of the graphite from 340mA·h / g to 360mA·h / g, for example, it can be 340mA·h / g, 345mA·h / g, 348mA·h / g, 350mA·h / g, 355mA·h / g, 358mA·h / g, 360mA·h / g, without specific limitation.

[0020] Optionally, the Cap value of the graphite is in the range of 358-360, with the unit of mA·h / g.

[0021] In order to increase the discharge capacity of the negative electrode active material, the Cap of graphite can be 358mA·h / g, 359mA·h / g, and 360mA·h / g.

[0022] Optionally, the discharge capacity of the graphite is defined as Cap, in units of mA·h / g, the average particle size of the graphite is defined as Dv50, in units of μm, and the oil absorption value of the graphite is defined as DBP, in units of cm 3 / 100g, then the Cap, the Dv50 and the DBP satisfy the relationship: 15≤Cap / 360*(DBP-53)+Dv50≤18.

[0023] The smaller the particle size of graphite, the larger the specific surface area of ​​graphite, the larger the discharge capacity of graphite, and the higher the oil absorption value of graphite. In order to balance the oil absorption value with a low range value under a large discharge capacity, Cap, Dv50 and DBP in this application satisfy the relationship: 15≤Cap / 360*(DBP-53)+Dv50≤18. Under the condition of satisfying this relationship, graphite with high energy density is obtained.

[0024] Optionally, the discharge capacity of the graphite is defined as Cap, in units of mA·h / g, and the tap density of the graphite is defined as TD, in units of g / cm 3 The specific surface area of ​​the graphite is BET, and the unit is m 2 / g, then the Cap, the TD and the BET satisfy the relationship: 1.2≤Cap / 360*(TD-1.1)+BET≤1.4.

[0025] It is understandable that graphite with high DBP value generally has low TD. In order to balance the oil absorption value with low range value under large discharge capacity, Cap, TD and BET satisfy the relationship: 1.2≤Cap / 360*(TD-1.1)+BET≤1.4. Under the condition of satisfying this relationship, graphite with high energy density is obtained.

[0026] The present application also provides a method for preparing graphite, comprising the following steps:

[0027] Providing needle coke, crushing, spheroidizing, coating, graphitizing and screening the needle coke to obtain graphite.

[0028] In the process of preparing graphite, needle coke is provided, the needle coke is crushed to obtain needle coke of suitable size, and then spheroidized and shaped. The shaped needle coke is further coated with a coating material, and then the coated needle coke is graphitized. Finally, impurities are removed through screening to obtain graphite.

[0029] Optionally, in the process of crushing, spheroidizing, coating, graphitizing and screening the needle coke to obtain graphite, the following steps are included:

[0030] The needle coke is crushed, spheroidized, screened, batched, coated, graphitized and screened to obtain graphite.

[0031] Optionally, in the step of batching the needle coke, the particle size range and weight fraction of the needle coke are as follows:

[0032] 10μm-15μm5-15 copies;

[0033] 15μm-25μm45-55 parts;

[0034] 25μm-30μm is 35-45 copies.

[0035] Three different particle sizes of needle coke are used to prepare carbon negative electrode materials, and small-particle needle coke with a large specific surface area, a short path for lithium ions to enter the center of the particle, and small resistance is mixed with large-particle needle coke with a small specific surface area, a long path for lithium ions to enter the center of the particle, large resistance and large particle size to achieve complementary advantages. After graphitization, the coated needle coke has a high overall graphitization degree, a large tap density and a small DBP value. The graphite is more conducive to the preparation of negative electrode materials with excellent performance, so that the battery has the characteristics of high battery capacity, high energy density, long cycle life and good fast charging performance. In addition, in the process of preparing the anode slurry, it is also beneficial to improve the filterability, that is, due to the more uniform size, the phenomenon that large particles are difficult to pass through the filter will not occur. In addition, when the anode slurry is filtered, large and small particles are matched to easily pass through the filter element. If all large particles pass through the filter element at the same time, the filter element is more likely to be blocked.

[0036] In the process of mixing the particle size range and weight proportion of needle coke, the range of 10μm-15μm is 5-15 parts, 15μm-25μm is 45-55 parts, and 25μm-30μm is 35-45 parts, and the DBP range value can be obtained as 45cm 3 / 100g-65cm 3 / 100g. If the small particle size fraction is too large, the specific surface area will increase and the DBP value will increase. If the large particle size fraction is too large, the specific surface area will decrease and the DBP value will decrease. Therefore, the particle size range and weight ratio of needle coke are selected within the above range.

[0037] Optionally, the step of batching the needle coke includes the following steps:

[0038] Needle coke with a particle size of 10 μm-15 μm is added to needle coke with a particle size of 15 μm-25 μm and mixed. After mixing evenly, mixed powder A is obtained. Then, the mixed powder A is poured into needle coke with a particle size of 25 μm-30 μm and mixed. After mixing evenly, the batching is completed.

[0039] Put small-particle needle coke into medium-particle needle coke and mix them first, so that the small and medium-particle needle cokes are evenly mixed to obtain a uniformly mixed mixed powder A, and then pour the mixed powder A into large-particle needle coke for mixing, so that the overall mixture has a uniform particle size distribution, and the small-particle needle coke is filled in the medium-particle needle coke, and the medium-particle needle coke is filled in the large-particle needle coke, so as to avoid a large amount of coating material filling into the gaps of the needle coke during the coating process.

[0040] Optionally, the step of pouring the mixed powder A into needle coke having a particle size of 25 μm-30 μm for mixing includes the following steps:

[0041] First, 1 / 3-1 / 2 of the mixed powder A by weight is poured into needle coke with a particle size of 25 μm-30 μm for mixing, and after stirring evenly, the remaining mixed powder A is poured into needle coke with a particle size of 25 μm-30 μm for mixing.

[0042] The mixed powder A is added to the component with larger particle size in batches, so that the gap formed is more matched with the particle size of the coating material, which is convenient for the coating material to coat the needle coke of different particle sizes and make the coated needle coke present a more uniform particle state. The above three particle sizes are mixed to make the coated product have a larger tap density and a smaller specific surface area.

[0043] Optionally, the step of coating the needle coke includes the following steps:

[0044] The needle coke obtained in the previous step is mixed with a coating material to obtain a coated product, wherein the weight ratio of the needle coke to the coating material is 80:(3-22).

[0045] According to the particle size ratio of needle coke, the weight fraction ratio of needle coke to coating material is selected to be 80:(3-22), and most of the obtained negative electrode material semi-finished products are in loose particles, with almost no exposed parts, which reduces the probability of the exposed part of the negative electrode material reacting with the solvent in the electrolyte during the first charge and discharge, thereby improving the first charge and discharge efficiency. The weight ratio of needle coke to coating material can be 80:3, 80:5, 80:10, 80:15, 80:20, 80:22, and is not specifically limited.

[0046] Optionally, the coating material includes at least one of graphite, amorphous carbon, asphalt, metal and oxides thereof;

[0047] And / or, the particle size of the coating material is 2 μm-4 μm.

[0048] By coating the needle coke with a coating material, the charge and discharge efficiency of the prepared graphite is improved. For example, the coating material can be one of graphite, amorphous carbon, asphalt, metal and its oxide, or a mixture of multiple materials, without specific limitation. The particle size of the coating material can be 2 μm, 3 μm, or 4 μm, without specific limitation.

[0049] Optionally, in the graphitization step, the following steps are included:

[0050] The coated product obtained through the coating step is placed in a graphitization furnace, and in an inert atmosphere, the temperature is first raised to 1300° C.-1700° C. for high-temperature carbonization;

[0051] The temperature is then raised to 2500°C-3200°C for graphitization, and after the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

[0052] The continuous heating steps are used for high-temperature carbonization and graphitization to achieve energy saving. The heating process of the graphitization workshop process temperature from 0-3200℃ includes the high-temperature carbonization process of the negative electrode material. If the negative electrode material is heated to 1300℃-1700℃ for high-temperature carbonization, then cooled to room temperature, and then heated to 2500-3200℃ for graphitization, it will increase the unit consumption of the product, thereby increasing the production cost.

[0053] Optionally, the step of placing the coated product obtained through the coating step into a graphitization furnace and first heating it to 1300° C.-1700° C. for high-temperature carbonization includes the following steps:

[0054] The coated product obtained through the coating step is placed in a graphitization furnace, and the temperature is first raised to 1300°C-1700°C at a heating rate of 50°C / min and kept at that temperature for 4 hours for high-temperature carbonization;

[0055] And / or, the step of heating to 2500° C.-3200° C. for graphitization, and then slowly cooling the graphitization furnace to room temperature to obtain a graphitized product comprises the following steps:

[0056] The temperature is raised to 2500-3200°C at a heating rate of 200°C / min, and the graphitization treatment is performed for 48h-72h. After the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

[0057] During the carbonization process, the coated product obtained after the coating step is placed in a graphitization furnace and heated to 1300°C-1700°C at a heating rate of 50°C / min and kept at this temperature for 4 hours for high-temperature carbonization. During this process, various reactions will take place, such as dehydrogenation reaction and condensation reaction, to decompose organic matter into residual carbon and volatile compounds and reduce impurities.

[0058] During the graphitization process, the temperature is increased at 200°C / min. Compared with traditional sintering, the heating rate is faster, the sintering temperature is higher, the degree of graphitization is higher, and the impurities are less.

[0059] The present application also provides an anode slurry, which includes a dispersant and the graphite.

[0060] Since the graphite in the present application has a low DBP value and a low oil absorption value, a small amount of binder is used in the process of preparing the anode slurry. In order to avoid the problem of uneven dispersion caused by insufficient binder, a dispersant is added in the process of preparing the anode slurry to improve the dispersibility of the graphite in the anode slurry, avoid the formation of filter residue, improve the filtration performance of the anode slurry during filtration, and improve the cycle performance of the electrode prepared by the anode slurry.

[0061] Optionally, the content of the dispersant accounts for 0.9%-1.5% of the solid matter content in the anode slurry.

[0062] By using a suitable amount of dispersant, there is no filter residue (filter residue refers to agglomerated large-particle graphite. Due to poor dispersibility, graphite particles form agglomerates to form large-particle filter residue), which avoids deterioration of filtration performance and prevents large-particle filter residue from being coated on the pole piece, thereby reducing cycle performance during charge and discharge. The content of the dispersant in the solid matter content of the anode slurry can be 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, and there is no specific limitation.

[0063] Optionally, the content of the dispersant accounts for 1.1%-1.3% of the solid matter content in the anode slurry.

[0064] The dispersant cannot be too much or too little. Too much will reduce the energy density of the electrode, while too little will lead to poor dispersion of graphite. The content of the dispersant can be 1.1%, 1.2%, or 1.3% of the solid matter content in the anode slurry, and there is no specific limitation.

[0065] Optionally, the discharge capacity of the graphite is defined as Cap, with a unit of mA·h / g, and the oil absorption value of the graphite is defined as DBP, with a unit of cm 3 / 100g, the content of the dispersant accounts for M of the solid matter content in the anode slurry, then the Cap, the DBP, and the M satisfy the relationship: 0.3%≤Cap / 360*(DBP-53) / 1000+M≤1.7%.

[0066] In the preparation process of anode slurry, the amount of dispersant used is related to the DBP value. The lower the DBP value, the more dispersant is needed to improve the dispersibility of graphite and reduce the amount of filter residue. In theory, the more dispersant, the better the graphite dispersibility, but too much dispersant will reduce the energy density. In order to balance the energy density, Cap, DBP, and M satisfy the relationship: 0.3%≤Cap / 360*(DBP-53) / 1000+M≤1.7%.

[0067] Optionally, the dispersant includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose, and ethoxy cellulose.

[0068] The dispersant may be a mixture of one or more of carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose, and ethoxy cellulose, without limitation.

[0069] The aqueous solution of carboxymethyl cellulose and substances with similar structures has the functions of thickening, film-forming, bonding, moisture retention, colloid protection, emulsification and suspension.

[0070] The above-mentioned dispersant can disperse the graphite particles very well, and further has a bonding effect. It can fully disperse the graphite to reduce the formation of filter residue, and can further strengthen the bonding force between the graphite and the electrode, thereby improving the cycle and fast charging performance. That is, it also has the functional effect of a binder to improve the bonding properties when the amount of binder is small.

[0071] The present application also provides a negative electrode plate, which includes a current collector and an anode slurry disposed on the current collector, wherein the anode slurry is the anode slurry described above.

[0072] In the preparation process of lithium-ion batteries, the quality of the slurry directly affects the performance of lithium-ion batteries. By coating the above-mentioned anode slurry with good dispersibility on the current collector, the performance of the battery can be improved.

[0073] The present application also provides a battery, comprising: a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate is the negative electrode plate described above.

[0074] The performance of the battery can be improved by coating the anode slurry with good dispersion on the current collector to prepare the negative electrode sheet.

[0075] The present application also provides an electrical device, which includes the battery.

[0076] As battery performance is improved, the performance of electrical equipment using the battery will also be improved.

[0077] The graphite of the present application is prepared from needle coke, and the oil absorption value DBP of the graphite ranges from 45 to 65, in units of cm 3 / 100g. Due to the high oil absorption value of graphite, more dispersant and binder will be consumed in the process of preparing anode slurry, increasing the cost. The oil absorption value of this application is 45cm 3 / 100g-65cm 3 / 100g, indicating that the exposed end face of the graphite is reduced. In the process of using the graphite as the negative electrode material to prepare the slurry, the consumption of dispersant and binder is reduced, which can reduce the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0079] Figure 1 The figure is a schematic diagram of the process for preparing graphite of the present invention;

[0080] Figure 2 This is a schematic diagram of improving the oil absorption value by combining large and small particles of the present invention.

[0081] Description of Figure Numbers:

[0082] Label name Label name 1 Large particles 4 Oil on particle surface 2 Medium Particles 5 Oil between particles 3 Small particles

[0083] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0084] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0086] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0087] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text is to include three parallel solutions. Taking "A and / or B as an example", it includes solution A, or solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0088] Batteries mentioned in this field can be divided into disposable batteries and rechargeable batteries according to whether they are rechargeable. Common types of rechargeable batteries currently include: lead-acid batteries, nickel-metal hydride batteries and lithium-ion batteries. Lithium-ion batteries are currently widely used in pure electric vehicles and hybrid vehicles. The capacity of lithium-ion batteries used for this purpose is relatively low, but they have larger output and charging current, and also have a longer service life, but the cost is higher.

[0089] The battery described in the embodiments of the present application refers to a rechargeable battery. The embodiments disclosed in the present application will be described below mainly by taking a lithium-ion battery as an example. It should be understood that the embodiments disclosed in the present application are applicable to any other appropriate type of rechargeable battery. The battery mentioned in the embodiments disclosed in the present application can be directly or indirectly applied to an appropriate device to power the device.

[0090] The battery mentioned in the embodiments disclosed in this application refers to a single physical module including one or more battery cells to provide a predetermined voltage and capacity. Battery cells are the basic units in the battery, and can generally be divided into: cylindrical battery cells, rectangular battery cells and soft-pack battery cells according to the packaging method. The following will mainly focus on rectangular battery cells. It should be understood that the embodiments described below are also applicable to cylindrical battery cells or soft-pack battery cells in some aspects.

[0091] A battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. Lithium-ion battery cells mainly rely on the movement of lithium ions between the positive electrode sheet and the negative electrode sheet to work. In cylindrical battery cells, the film structure of three layers of material is wound into a cylindrical electrode assembly, while in rectangular battery cells, the film structure is wound or stacked into an electrode assembly with a roughly rectangular shape.

[0092] In a common battery cell structure, the battery cell includes a shell, an electrode assembly and an electrolyte. The electrode assembly is contained in the shell of the battery cell, and the electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The shell includes a shell and an end cap. The shell includes a housing formed by a plurality of walls and an opening. The end cap is arranged at the opening to close the housing chamber. In addition to the electrode assembly, the housing chamber also contains an electrolyte. The positive electrode sheet and the negative electrode sheet in the electrode assembly include tabs. In order to ensure that a large current passes without melting, the number of positive tabs is multiple and stacked together, and the number of negative tabs is multiple and stacked together. The tabs are electrically connected to the electrode terminals located outside the battery cell through connecting members, and the electrode terminals generally include a positive electrode terminal and a negative electrode terminal. For a rectangular battery cell, the electrode terminal is generally arranged at the end cap portion. A plurality of battery cells are connected in series and / or in parallel via the electrode terminals for application in various applications.

[0093] In some high-power applications such as electric vehicles, the application of batteries includes three levels: battery cells, battery modules and batteries. The battery module is formed by electrically connecting a certain number of battery cells together and placing them in a frame in order to protect the battery cells from external impact, heat, vibration, etc. The battery refers to the final state of the battery system installed in the electric vehicle. The battery generally includes a box for encapsulating one or more battery cells. The box generally consists of a cover and a box shell.

[0094] A plurality of mounting points for connecting with the vehicle body are arranged on the frame of the box body or in the middle of the box shell. In order to improve the stability of the connection between the vehicle body and the battery, mounting parts are often arranged at the mounting points.

[0095] In some battery production and processing technologies, multiple battery cells are first integrated into a battery module, and then the battery module is packaged in a battery box to form a battery pack / battery box.

[0096] Commonly used battery modules generally include two end plates, between which multiple battery cells are arranged. The end plate with the output pole of the battery module is also called the output pole end plate, and the end plate without the output pole of the battery module is also called the non-output pole end plate.

[0097] A battery pack may contain multiple battery modules in one row or multiple rows. The arrangement of multiple rows of multiple battery modules may be double rows and multiple columns, multiple rows and double columns, multiple rows and multiple columns, etc. Taking a battery pack containing double rows and multiple columns of battery modules as an example, the first end plate of each column is generally a head output extreme plate, the two adjacent end plates between two rows of battery modules are middle non-output extreme plates, the last end plate of each column is a tail non-output extreme plate, the head output extreme plate and one of the middle non-output extreme plates belong to the first row of battery modules, and one of the middle non-output extreme plates and the tail output extreme plate belong to the second row of battery modules.

[0098] The battery module needs to be packaged into the battery box with the help of tooling, which is generally equipped with a clamping mechanism for clamping the battery module, such as a clamping claw, a suction cup, etc. When a tooling with a clamping claw is used to package the battery module, a clamping claw groove that matches the clamping claw is generally provided on the side of the end plate away from the battery cell, so that the clamping claw can be inserted to clamp and transport the battery module.

[0099] The development of battery technology must take into account many design factors at the same time, such as energy density, cycle life, discharge capacity, charge and discharge rate and other performance parameters. In addition, the production cost and processing technology of the battery must also be considered to improve the quality and production efficiency of the battery.

[0100] Needle coke is a high-quality variety of carbon material that is being vigorously developed. The large atomic clusters inside needle coke (containing less sulfur impurities) are roughly stacked in parallel and oriented, with few cross-connections and easy graphitization. Its appearance is a silver-gray, metallic-luster porous solid. Its structure has obvious flow texture, large and few pores that are slightly elliptical, and the particles have a large aspect ratio, with a fibrous or needle-like texture and a lubricious feel. It is the raw material for the production of high-end carbon products such as ultra-high power electrodes, special carbon materials, carbon fibers and their composite materials.

[0101] The development direction of the next generation of graphite technology is high specific energy and fast charging. Graphite uses calcined needle coke, which has a higher degree of graphitization and increased gram capacity. However, the surface layer has more layered structures, is brittle and easy to crack, and exposes more end faces. For the convenience of visual understanding, the end face can be understood as the opening on the surface of the particle that connects the internal pores of the particle. Since there are more openings exposed to the outside, the oil absorption value of the graphite itself is increased. The size of the oil absorption value is related to the particle size distribution, particle shape, degree of dispersion and agglomeration, specific surface area and surface properties of the material.

[0102] Oil absorption value is DBP value, unit is cm 3 / 100g. Under the specified test conditions, the volume (cm2) of dibutyl phthalate (DBP, di-n-butyl phthalate) absorbed by 100g of material 3 ) number. It is generally used to characterize the degree of aggregation of material particles. Graphite has a large oil absorption value, and more dispersants and binders will be consumed in the process of preparing anode slurry, increasing costs.

[0103] In order to effectively utilize needle coke, it is prepared into graphite to reduce the cost of graphite in electrode applications.

[0104] The present application provides a graphite, which is prepared from needle coke, and the oil absorption value DBP of the graphite ranges from 45 to 65, with the unit of cm 3 / 100g.

[0105] Due to the high oil absorption value of graphite, more dispersants and binders will be consumed in the process of preparing anode slurry, increasing costs. The oil absorption value of this application is 45cm 3 / 100g-65cm 3 / 100g, indicating that the exposed end face of graphite is reduced. In the process of using the graphite as the negative electrode material to prepare the slurry, the consumption of dispersant and binder is reduced, which can reduce the cost. The oil absorption value can be 45cm 3 / 100g、47cm 3 / 100g、49cm 3 / 100g、50cm 3 / 100g、52cm 3 / 100g、54cm 3 / 100g、56cm 3 / 100g、58cm 3 / 100g、59cm 3 / 100g、60cm 3 / 100g、63cm 3 / 100g、65cm 3 / 100g, not specifically limited.

[0106] Furthermore, the DBP of graphite is 50-53, in cm 3 / 100g.

[0107] In the process of preparing anode slurry, if the oil absorption value of graphite is too high, it will lead to more consumption of dispersant and binder, and increase the cost. However, if the oil absorption value of graphite is too low, it will lead to poor dispersibility when the amount of binder is small. Therefore, the oil absorption value should not be too high or too low. The DBP of graphite can be 50cm 3 / 100g、51cm 3 / 100g、52cm 3 / 100g、53cm 3 / 100g, not specifically limited.

[0108] Furthermore, the graphitization degree G of the graphite is greater than 94%.

[0109] The graphitization process is to gradually transform the disordered hexagonal carbon atom planes in the two-dimensional space of carbon materials into overlapping three-dimensional ordered spaces.

[0110] The degree of graphitization refers to the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure. The closer the lattice size is to the lattice parameters of ideal graphite, the higher the degree of graphitization. Therefore, the unit cell parameters of carbon crystals can be directly used to characterize their degree of graphitization. The XRD method uses the lattice constant of graphite to calculate the degree of graphitization G:

[0111] G=(0.344-d002) / (0.344-0.3354)*100%

[0112] Where: 0.3440 is the (002) crystal plane spacing of completely non-graphitized carbon, nm; 0.3354 is the (002) crystal plane spacing of ideal graphite crystal, nm. d002 is the (002) crystal plane spacing of actual graphite sample, nm.

[0113] The graphite in this application has a graphitization degree G greater than 94%. The higher the graphitization degree G, the more regular the carbon material structure and the larger the specific surface area. When the graphite is used in the negative electrode plate, the electrolyte wetting performance of the negative electrode plate can be improved, the lithium ion transmission path can be shortened during the charge and discharge process, and the fast charge and cycle performance of the battery can be improved. The graphitization degree G can be 94.1%, 95%, 96%, 97%, 98%, 99%, 100%, and there is no specific limitation.

[0114] Furthermore, the BET specific surface area of ​​graphite is in the range of 0.9-1.5, in m 2 / g.

[0115] The large specific surface area means that graphite can accommodate more lithium ions, which is beneficial to increase the battery capacity. The specific surface area of ​​graphite BET can be 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 14m 2 / g, 1.5m 2 / g, no specific limit.

[0116] Furthermore, the BET value of graphite ranges from 1.2 to 1.4, in m 2 / g.

[0117] It is understandable that a low specific surface area will result in a low oil absorption value. In order to obtain an appropriate range of oil absorption values, the value range of the specific surface area cannot be too large. The BET of graphite can be 1.2 m 2 / g, 1.3m 2 / g, 1.4m 2 / g, no specific limit.

[0118] Furthermore, the tap density TD of graphite ranges from 0.9 to 1.4, in g / cm 3 .

[0119] Tap density refers to the density of powder after it is filled into a specific container and the container is vibrated to destroy the voids in the powder and make the powder in a tightly packed state. By measuring the tap density, we can know the flowability and porosity of the powder.

[0120] The high tap density indicates that in the process of applying graphite to the negative electrode, a thinner active material layer can be prepared, so that more lithium ions can be stored in the same volume, thereby improving the energy density. The tap density TD of graphite can be 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 It is understood that the tap density is affected by the particle size of the material, and when the average particle size Dv50 of graphite is in the range of 10 μm-20 μm, the tap density TD in the above range can be obtained.

[0121] Furthermore, the TD of graphite is 1.0-1.1, expressed in g / cm 3 .

[0122] The tap density cannot be too large. If the tap density is too large, lithium ions are not easily embedded, which deteriorates fast charging. It is understandable that a large tap density reduces the number of pores, which is not conducive to electrolyte infiltration, and lithium ions cannot be transmitted in time, thus deteriorating fast charging. Therefore, the TD of graphite can be 1.0g / cm 3 or 1.1 g / cm 3 It is understood that the tap density is affected by the particle size of the material, and the Dv50 of graphite is in the range of 14 μm-16 μm, and the tap density TD in the above range can be obtained.

[0123] Furthermore, the discharge capacity Cap of graphite ranges from 340 to 360, with the unit being mA·h / g.

[0124] The graphite of the present application can satisfy the range value of the discharge capacity Cap of the graphite from 340mA·h / g to 360mA·h / g, for example, it can be 340mA·h / g, 345mA·h / g, 348mA·h / g, 350mA·h / g, 355mA·h / g, 358mA·h / g, 360mA·h / g, without specific limitation.

[0125] Further, the Cap of graphite is 358-360, and the unit is mA·h / g.

[0126] In order to increase the discharge capacity of the negative electrode active material, the Cap of graphite can be 358mA·h / g, 359mA·h / g, and 360mA·h / g.

[0127] Furthermore, the discharge capacity of graphite is defined as Cap, in units of mA·h / g, the average particle size of graphite is Dv50, in units of μm, and the oil absorption value of graphite is DBP, in units of cm 3 / 100g, then Cap, Dv50 and DBP satisfy the relationship: 15≤Cap / 360*(DBP-53)+Dv50≤18.

[0128] The smaller the particle size of graphite, the larger the specific surface area of ​​graphite, the larger the discharge capacity of graphite, and the higher the oil absorption value of graphite. In order to balance the oil absorption value with a low range value under a large discharge capacity, Cap, Dv50 and DBP in this application satisfy the relationship: 15≤Cap / 360*(DBP-53)+Dv50≤18. Under the condition of satisfying this relationship, graphite with high energy density is obtained.

[0129] Furthermore, the discharge capacity of graphite is defined as Cap, with the unit of mA·h / g, and the tap density of graphite is defined as TD, with the unit of g / cm 3 , the specific surface area of ​​graphite is BET, the unit is m 2 / g, then Cap, TD and BET satisfy the relationship: 1.2≤Cap / 360*(TD-1.1)+BET≤1.4.

[0130] It is understandable that graphite with high DBP value generally has low TD. In order to balance the oil absorption value with low range value under large discharge capacity, Cap, TD and BET satisfy the relationship: 1.2≤Cap / 360*(TD-1.1)+BET≤1.4. Under the condition of satisfying this relationship, graphite with high energy density is obtained.

[0131] The graphite of the present application has the characteristics of high graphitization degree, high tap density and low DBP value. The graphite is more conducive to the preparation of negative electrode materials with excellent performance, so that the battery has the characteristics of high battery capacity, high energy density, long cycle life and good fast charging performance. In addition, in the process of preparing the anode slurry, it is also beneficial to improve the filterability. For example, after preparing the anode slurry, before coating the anode slurry, a filtering step is required to remove impurities. The anode slurry prepared by the graphite of the present application has good fluidity and saves filtration time. Specifically, the DBP value is small. In the process of preparing the anode slurry, the amount of binder and dispersant can be reduced. A small amount of binder and dispersant is sufficient to make the graphite particles evenly dispersed and orderly connected. At this time, avoid using a large amount of binder and dispersant, the viscosity increases, and the graphite particles are bonded together. During filtration, the graphite particles bonded together form large particles, which are difficult to pass through a mesh of a certain size, slowing down the filtration step.

[0132] The present application also provides a method for preparing graphite, such as Figure 1 As shown, the process comprises the following steps: providing needle coke, and crushing, spheroidizing, coating, graphitizing, and screening the needle coke to obtain graphite.

[0133] In the process of preparing graphite from needle coke, the needle coke raw material is first crushed, that is, the large particles are turned into small particles, and then spheroidized. Spheroidization means that under the impact of high-speed airflow and rotor, the graphite powder is quickly curled, balled, and compacted due to the mutual collision, friction, and shearing between particles. After spheroidization, the aspect ratio of the graphite powder becomes smaller, the sphericity coefficient is greatly improved, the anisotropic effect is reduced, the particle size distribution is narrowed, and the loose density and tap density are greatly increased.

[0134] Coating refers to coating the surface of a material with a conductive substance to improve conductivity. For example, the composite of natural graphite with metals and metal oxides is mainly achieved by deposition on the graphite surface. By coating the graphite surface with a layer of metal (Ag, Ni, Sn, Zn, Al, etc.), the charge transfer resistance can be effectively reduced, the diffusion coefficient of lithium can be increased, thereby inhibiting the decomposition of the electrolyte on the graphite surface and improving the electrochemical properties of the material. In addition, coating metals and their oxides (NiO, MoO3, CuO, Fe2O3, etc.) can prevent the reaction between the electrolyte and graphite to a certain extent, reduce the irreversible capacity of the material, and improve the charge and discharge efficiency.

[0135] Graphitization is the process of gradually transforming the disordered hexagonal carbon atom planes of carbon materials into three-dimensional ordered overlapping spaces. Graphitization can rearrange carbon atoms to obtain good thermal conductivity and low thermal expansion coefficient, and can remove impurities and increase purity.

[0136] For example, graphitization starts at 1700℃. During the temperature increase, the crystal grows, the degree of graphitization increases, and the interlayer spacing decreases. In the graphite layer, the carbon atoms are arranged hexagonally and extend in the two-dimensional direction. Each carbon atom between the layers exists in the form of a strong sp2 hybrid σ bond structure with its three adjacent carbon atoms, and the structure is quite stable. Between the graphite layers, carbon-carbon is only bonded by a weak van der Waals force, and the interlayer spacing is about 0.34nm. Due to the weak bonding force between graphite layers and the large space, it is easy to insert other metal or non-metal molecules, atoms, ions or ion clusters to form graphite interlayer compounds.

[0137] In the process of preparing graphite, needle coke is provided, the needle coke is crushed to obtain needle coke of suitable size, and then spheroidized and shaped. The shaped needle coke is further coated with a coating material, and then the coated needle coke is graphitized. Finally, impurities are removed through screening to obtain graphite.

[0138] Furthermore, in the process of crushing, spheroidizing, coating, graphitizing and screening needle coke to obtain graphite, the following steps are included: crushing, spheroidizing, screening, batching, coating, graphitizing and screening needle coke to obtain graphite.

[0139] Since needle coke has the characteristics of uneven size and structure, in order to make full use of needle cokes of different sizes to improve its uniformity, the needle coke is screened after the spheroidization step, that is, the materials of different sizes obtained after spheroidization are classified, and the materials within a certain size range are classified into one category; then the batching step is carried out, that is, the materials of different size grades obtained by screening are remixed so that small-sized particles can enter the gaps of large-sized particles, that is, particle grading, small particle powder is removed, and the DBP value is reduced. Specifically, Figure 2 As shown, when large and small particles are matched, small particles will enter the gaps of large particles and stack relatively tightly, which will reduce the DBP value and help increase the tap density.

[0140] Furthermore, in the step of batching the needle coke, the particle size range and weight proportions of the needle coke are as follows: 10 μm-15 μm, 5-15 parts; 15 μm-25 μm, 45-55 parts; 25 μm-30 μm, 35-45 parts.

[0141] Three different particle sizes of needle coke are used to prepare carbon negative electrode materials, and small-particle needle coke with a large specific surface area, a short path for lithium ions to enter the center of the particle, and small resistance is mixed with large-particle needle coke with a small specific surface area, a long path for lithium ions to enter the center of the particle, large resistance and large particle size to achieve complementary advantages. After graphitization, the coated needle coke has a high overall graphitization degree, a large tap density and a small DBP value. The graphite is more conducive to the preparation of negative electrode materials with excellent performance, so that the battery has the characteristics of high battery capacity, high energy density, long cycle life and good fast charging performance. In addition, in the process of preparing the anode slurry, it is also beneficial to improve the filterability, that is, due to the more uniform size, the phenomenon that large particles are difficult to pass through the filter will not occur. In addition, when the anode slurry is filtered, large and small particles are matched to easily pass through the filter element. If all large particles pass through the filter element at the same time, the filter element is more likely to be blocked. Among them, 10μm-15μm can be 5 parts, 15μm-25μm can be 45 parts, and 25μm-30μm can be 35 parts; 10μm-15μm can be 10 parts, 15μm-25μm can be 50 parts, and 25μm-30μm can be 40 parts; 10μm-15μm can be 15 parts, 15μm-25μm can be 55 parts, and 25μm-30μm can be 45 parts, and there is no specific limitation.

[0142] In the process of mixing the particle size range and weight proportion of needle coke, the range of 10μm-15μm is 5-15 parts, 15μm-25μm is 45-55 parts, and 25μm-30μm is 35-45 parts, and the DBP range value can be obtained as 45cm 3 / 100g-65cm 3 / 100g. If the small particle size fraction is too large, the specific surface area will increase and the DBP value will increase. If the large particle size fraction is too large, the specific surface area will decrease and the DBP value will decrease. Therefore, the particle size range and weight ratio of needle coke are selected within the above range.

[0143] Furthermore, the material particle size distribution and tap density were further optimized to meet the requirements of 0.9 g / cm 3 -1.4g / cm 3 The combination of large and small particles helps to fill the gaps and improve the compaction density of the powder, and also facilitates the compaction of the pole piece to increase the energy density. In addition, it can also improve the slurry processability and obtain graphite with better fast charging and cycling.

[0144] It is understandable that small particles enter the gaps of large particles, and the small particles are coated with conductive materials, which improves the conductivity inside the large particles, thereby improving fast charging.

[0145] In addition, the improvement of the battery's cyclability is mainly caused by processability. In the process of preparing the anode slurry, the appearance of filter residue is avoided (filter residue refers to large-particle graphite with agglomerated size. Due to poor dispersion, graphite particles are agglomerated to form large-particle filter residue), thereby preventing large-particle filter residue from coating on the electrode and reducing the battery's cyclability.

[0146] It is understandable that the filter residue affects the cyclability. The filter residue particles are large and the binder coating area is small. The binder can store and transport the electrolyte. Lithium ions enter and exit the particles through the electrolyte. There is no binder inside the large particles, making it difficult for the electrolyte to infiltrate the large particles. The area and space inside the large particles cannot be effectively utilized, resulting in capacity loss and poor cyclability. Moreover, even if the electrolyte can penetrate into the large particles, it takes more time, which hinders the transport of lithium ions and reduces the rate performance.

[0147] Furthermore, in the step of batching the needle coke, the following steps are included: putting needle coke with a particle size of 10μm-15μm into needle coke with a particle size of 15μm-25μm for mixing, and obtaining mixed powder A after uniform mixing; and then pouring the mixed powder A into needle coke with a particle size of 25μm-30μm for mixing, and the batching is completed after uniform mixing.

[0148] Put small-particle needle coke into medium-particle needle coke and mix them first, so that the small and medium-particle needle cokes are evenly mixed to obtain a uniformly mixed mixed powder A, and then pour the mixed powder A into large-particle needle coke for mixing, so that the overall mixture has a uniform particle size distribution, and the small-particle needle coke is filled in the medium-particle needle coke, and the medium-particle needle coke is filled in the large-particle needle coke, so as to avoid a large amount of coating material filling into the gaps of the needle coke during the coating process.

[0149] Furthermore, the step of pouring the mixed powder A into the needle coke with a particle size of 25 μm-30 μm for mixing includes the following steps: first pouring 1 / 3-1 / 2 weight portion of the mixed powder A into the needle coke with a particle size of 25 μm-30 μm for mixing, stirring evenly, and then pouring the remaining mixed powder A into the needle coke with a particle size of 25 μm-30 μm for mixing.

[0150] The mixed powder A is added to the component with larger particle size in batches, so that the gap formed is more matched with the particle size of the coating material, which is convenient for the coating material to coat the needle coke of different particle sizes and make the coated needle coke present a more uniform particle state. The above three particle sizes are mixed to make the coated product have a larger tap density and a smaller specific surface area.

[0151] Furthermore, the step of coating the needle coke includes the following steps: mixing the needle coke obtained in the previous step with a coating material to obtain a coated product, wherein the weight ratio of the needle coke to the coating material is 80:(3-22).

[0152] According to the particle size ratio of needle coke, the weight fraction ratio of needle coke to coating material is selected to be 80:(3-22), and most of the obtained negative electrode material semi-finished products are in loose particles, with almost no exposed parts, which reduces the probability of the exposed part of the negative electrode material reacting with the solvent in the electrolyte during the first charge and discharge, thereby improving the first charge and discharge efficiency. The weight ratio of needle coke to coating material can be 80:3, 80:5, 80:10, 80:15, 80:20, 80:22, and is not specifically limited.

[0153] Further, the coating material includes at least one of graphite, amorphous carbon, asphalt, metal and oxides thereof; and / or the particle size of the coating material is 2 μm-4 μm.

[0154] By coating the needle coke with a coating material, the charge and discharge efficiency of the prepared graphite is improved. For example, the coating material can be one of graphite, amorphous carbon, asphalt, metal and its oxide, or a mixture of multiple materials, without specific limitation. The particle size of the coating material can be 2 μm, 3 μm, or 4 μm, without specific limitation.

[0155] Furthermore, in the graphitization step, the following steps are included: placing the coated product obtained in the coating step into a graphitization furnace, and first heating it to 1300°C-1700°C for high-temperature carbonization under an inert atmosphere; then heating it to 2500°C-3200°C for graphitization, and after the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

[0156] The continuous heating steps are used for high-temperature carbonization and graphitization to achieve energy saving. The heating process of the graphitization workshop process temperature from 0-3200℃ includes the high-temperature carbonization process of the negative electrode material. If the negative electrode material is heated to 1300℃-1700℃ for high-temperature carbonization, then cooled to room temperature, and then heated to 2500-3200℃ for graphitization, it will increase the unit consumption of the product, thereby increasing the production cost.

[0157] Further, in the step of placing the coated product obtained by the coating step into a graphitization furnace, and first heating it to 1300°C-1700°C for high-temperature carbonization, the following steps are included: placing the coated product obtained by the coating step into a graphitization furnace, heating it to 1300°C-1700°C at a heating rate of 50°C / min, and keeping it warm for 4 hours for high-temperature carbonization; and / or, heating it to 2500°C-3200°C for graphitization, and after the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained, including the following steps: heating it to 2500°C-3200°C at a heating rate of 200°C / min, graphitizing it for 48h-72h, and after the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

[0158] During the carbonization process, the coated product obtained after the coating step is placed in a graphitization furnace and heated to 1300°C-1700°C at a heating rate of 50°C / min and kept at this temperature for 4 hours for high-temperature carbonization. During this process, various reactions will take place, such as dehydrogenation reaction and condensation reaction, to decompose organic matter into residual carbon and volatile compounds and reduce impurities.

[0159] During the graphitization process, the temperature is increased at 200°C / min. Compared with traditional sintering, the heating rate is faster, the sintering temperature is higher, the degree of graphitization is higher, and the impurities are less.

[0160] In the present application, a single high-quality needle coke raw material is used, which is isotropic and sintered at a higher temperature to obtain graphite with a high degree of graphitization; in addition, the needle coke has a combination of large and small particles, and the small particles will enter the gaps of the large particles, stacking relatively tightly, thereby reducing the DBP value.

[0161] The present application also provides an anode slurry, which includes the above-mentioned graphite and a dispersant. Since the graphite adopts all the technical solutions of all the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0162] In the process of preparing lithium-ion batteries, the quality of the slurry directly affects the performance of the lithium-ion batteries. Uniform and stable slurry is crucial for preparing lithium-ion batteries with good performance.

[0163] Since the graphite in the present application has a low DBP value and a low oil absorption value, a small amount of binder is used in the process of preparing the anode slurry. In order to avoid the problem of uneven dispersion caused by insufficient binder, a dispersant is added in the process of preparing the anode slurry to improve the dispersibility of the graphite in the anode slurry, avoid the formation of filter residue, improve the filtration performance of the anode slurry during filtration, and improve the cycle performance of the electrode prepared by the anode slurry.

[0164] Furthermore, the content of the dispersant accounts for 0.9%-1.5% of the solid matter content in the anode slurry.

[0165] By using a suitable amount of dispersant, there is no filter residue (filter residue refers to agglomerated large-particle graphite. Due to poor dispersibility, graphite particles form agglomerates to form large-particle filter residue), which avoids deterioration of filtration performance and prevents large-particle filter residue from being coated on the pole piece, thereby reducing cycle performance during charge and discharge. The content of the dispersant in the solid matter content of the anode slurry can be 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, and there is no specific limitation.

[0166] It is understandable that the formation of filter residue is due to the poor dispersion of graphite particles in the slurry, which causes some graphite particles to agglomerate before contacting the binder, forming large-particle filter residue. There is no binder inside the large-particle filter residue, and the surface of the large-particle filter residue is coated with a binder, which affects the cyclicity. It is understandable that the filter residue particles are large and the binder coating area is small. The binder can store and transport the electrolyte. Lithium ions enter and exit the particles through the electrolyte. There is no binder inside the large particles, making it difficult for the electrolyte to infiltrate the inside of the large particles, and it is impossible to effectively use the area and space inside the large particles, resulting in capacity loss and poor cyclicity. Moreover, even if the electrolyte can penetrate into the large particles, it takes more time, which hinders the transport of lithium ions and reduces the rate performance.

[0167] Furthermore, the content of the dispersant accounts for 1.1%-1.3% of the solid matter content in the anode slurry.

[0168] The dispersant cannot be too much or too little. Too much will reduce the energy density of the electrode, while too little will lead to poor dispersion of graphite. The content of the dispersant can be 1.1%, 1.2%, or 1.3% of the solid matter content in the anode slurry, and there is no specific limitation.

[0169] Furthermore, the discharge capacity of graphite is defined as Cap, with the unit of mA·h / g, and the oil absorption value of graphite is DBP, with the unit of cm 3 / 100g, the content of dispersant accounts for the solid matter content in the anode slurry is M, then Cap, DBP, and M satisfy the relationship: 0.3%≤Cap / 360*(DBP-53) / 1000+M≤1.7%.

[0170] In the preparation process of anode slurry, the amount of dispersant used is related to the DBP value. The lower the DBP value, the more dispersant is needed to improve the dispersibility of graphite and reduce the amount of filter residue. In theory, the more dispersant, the better the graphite dispersibility, but too much dispersant will reduce the energy density. In order to balance the energy density, Cap, DBP, and M satisfy the relationship: 0.3%≤Cap / 360*(DBP-53) / 1000+M≤1.7%.

[0171] In the process of preparing anode slurry, less binder will cause graphite agglomeration. An appropriate amount of dispersant can improve the kneading properties of the anode slurry and avoid agglomeration to form filter residue. It can be understood that under the condition of good dispersion effect, the ideal situation is that each graphite is covered with binder to avoid the aggregation of multiple graphite particles. The aggregated large particles are wrapped by the binder to form filter residue; when each graphite is covered with binder, the graphite can be fully bonded to the electrode sheet, thereby improving the bonding between the active material and the electrode sheet in the anode slurry. Thanks to the enhanced bonding effect, the bonding force between the component particles after the electrode sheet is rolled is also enhanced, and the bonded electrode sheet is not easy to lose powder, thereby greatly improving the performance and service life of the lithium-ion battery.

[0172] Furthermore, the dispersant includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose, and ethoxy cellulose.

[0173] The dispersant may be a mixture of one or more of carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose, and ethoxy cellulose, without limitation.

[0174] The aqueous solution of carboxymethyl cellulose and substances with similar structures has the functions of thickening, film-forming, bonding, moisture retention, colloid protection, emulsification and suspension.

[0175] The above-mentioned dispersant can disperse the graphite particles very well, and further has a bonding effect. It can fully disperse the graphite to reduce the formation of filter residue, and can further strengthen the bonding force between the graphite and the electrode, thereby improving the cycle and fast charging performance. That is, it also has the functional effect of a binder to improve the bonding properties when the amount of binder is small.

[0176] Theoretically, graphite with a high DBP value consumes an increased amount of dispersant. In the present application, by optimizing the DBP of graphite, the amount of dispersant used in the preparation of anode slurry can be reduced, thereby increasing the energy density. Moreover, this type of low DBP graphite has good adhesion to carboxymethyl cellulose dispersant, which can increase the adhesion of the electrode, thereby improving the cycle and fast charging.

[0177] The present application also provides a negative electrode sheet, which includes a current collector and an anode slurry disposed on the current collector, wherein the anode slurry is the anode slurry described above. Since the anode slurry adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.

[0178] In the preparation process of lithium-ion batteries, the quality of the slurry directly affects the performance of lithium-ion batteries. By coating the above-mentioned anode slurry with good dispersibility on the current collector, the performance of the battery can be improved.

[0179] The present application also provides a battery, including: a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet. Since the negative electrode sheet adopts all the technical solutions of all the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0180] The performance of the battery can be improved by coating the anode slurry with good dispersion on the current collector to prepare the negative electrode sheet.

[0181] The present application also provides an electrical device, including a battery. Since the battery adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0182] The battery performance is improved, and the performance of the electrical equipment using the battery is also improved. For example, the electrical equipment can be a car, a ship, a train, etc., without specific limitation.

[0183] The graphite provided in this application has a DBP value of 45 cm 3 / 100g-65cm 3 / 100g range, avoiding the consumption of more dispersants and binders, and avoiding increased costs; at the same time, in the process of preparing the slurry, a suitable amount of dispersant is added to make the graphite dispersed evenly, improve the rheological properties of the slurry, improve the filterability, and achieve a good coating effect. By optimizing the graphite parameters and adjusting the anode slurry formula, a stable anode slurry is prepared, and ultimately a high specific energy and long-life lithium battery is obtained.

[0184] Example

[0185] Example 1

[0186] Preparation of graphite

[0187] Providing needle coke, crushing the needle coke, and changing the large particles of raw materials into small particles; spheroidizing, using spheroidizing equipment, spheroidizing the crushed needle coke at a set spheroidizing speed (1000r / min); screening, screening the needle coke after the spheroidizing step, that is, classifying the materials of different sizes obtained after spheroidization, and classifying the materials of a certain size range into one category (10μm-15μm is one category, 15μm-25μm is one category, and 25μm-30μm is one category); batching, mixing a certain number of needle cokes of different particle size ranges (10 parts of 10μm-15μm, 50 parts of 15μm-25μm, 25μm-30μm 40 parts) to obtain the batched needle coke; the batched needle coke is coated with a coating material (NiO, 2μm-4μm, the weight ratio of needle coke to coating material is 80:4), and the coated needle coke is further graphitized (at a heating rate of 50°C / min, first heated to 1500°C and kept warm for 4h, and then heated to 3000°C at a heating rate of 200°C / min, and graphitized for 50h, and the graphitization furnace is slowly cooled to room temperature to obtain a graphitized product), and finally impurities are removed by screening to obtain graphite (Dv50 is 18μm).

[0188] Preparation of lithium-ion batteries

[0189] 1) Preparation of negative electrode

[0190] Preparation of anode slurry: solid matter is mixed with solvent to form slurry; solid matter includes active material graphite, silicon, conductive agent acetylene black, high molecular polymer, carboxymethyl cellulose.

[0191] The specific steps are: dissolve active material graphite, silicon, conductive agent acetylene black, high molecular polymer, and carboxymethyl cellulose (CMC) in solvent deionized water at a weight ratio of 90:5:2:1.9:1.1, mix them evenly to prepare negative electrode slurry, coat the slurry on copper foil, dry it, and then cold press and cut it to obtain anode electrode sheets.

[0192] 2) Preparation of positive electrode

[0193] The positive electrode active material NCM, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.5:1.5:2, and the positive electrode slurry is obtained after being fully stirred and mixed. Then, the positive electrode slurry is evenly coated on the positive electrode collector with a primer, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0194] 3) Diaphragm

[0195] The diaphragm is a PE diaphragm with PVDF and alumina coating on the surface to improve adhesion and heat resistance.

[0196] 4) Electrolyte

[0197] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6:LiFSI (2:8) is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of lithium salt is 1 mol / L.

[0198] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then wound to obtain a bare cell, the tabs are welded to the bare cell, and the bare cell is placed in an aluminum shell and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then goes through the processes of static, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a lithium-ion battery product.

[0199] As shown in Table 1, on the basis of Example 1, the experimental parameters were changed (the experimental parameters are shown in Table 1 below) to obtain the experimental data of Examples 2 to 13 and Comparative Examples 1 to 3.

[0200] Performance Testing

[0201] The tap density of graphite is tested in accordance with GB / T5162-1985 Metal Powder-Determination of Tap Density, and the specific surface area of ​​graphite is tested in accordance with GB / T19587-2004 Gas Adsorption BET Method for Determination of Specific Surface Area of ​​Solids.

[0202] Battery capacity test:

[0203] ①Stand still for 30min; ②1 / 3C charge to 4.25V, 4.25V constant voltage charge to 0.05C and end; ③Stand still for 30min; ④1 / 3C discharge to 2.8V to get capacity C0; The energy obtained is the battery energy, weight energy density = energy / battery weight.

[0204] Battery lithium deposition test:

[0205] ①Stand still for 5 minutes; ②Discharge 1 / 3C0 to 2.8V; ③Stand still for 5 minutes; ④Charge 1.2C0 to 50% SOC; ⑤Charge 0.87C0 to 80% SOC; ⑥Charge 1 / 3C0 to 4.25V, and charge at 4.25V constant voltage to 0.05C; ⑦Stand still for 10 minutes; ⑧Discharge 1 / 3C0 to 2.8V; ⑨Stand still for 5 minutes; ⑩Repeat steps 4-9 5 times; 1 / 3C charge to 4.25V, 4.25V constant voltage charge to 0.05C end; Let stand for 5 minutes.

[0206] Battery cycle test:

[0207] Adjust the temperature to 45°C and keep warm for 2 hours.

[0208] ①Rest for 5min; ②1 / 3C charge to 4.25V, 4.25V constant voltage charge to 0.05C; ③Stand for 5min; ④0.5C0 discharge to 2.8V; ⑤Stand for 5min; ⑥Repeat steps 7-9 until capacity fading≤80%.

[0209] Table 1 Experimental parameters and graphite performance parameters in the preparation process of graphite materials

[0210]

[0211] Table 2 Dispersant addition parameters in anode slurry and battery performance parameters

[0212]

[0213] Data analysis

[0214] It can be seen from the data in Table 1 above that in the spheroidization step, as shown in Examples 1 to 4, the spheroidization speed decreases and the DBP value decreases. The reason is that the higher the spheroidization speed, the smaller the particle size and the larger the BET. This results in an increase in the amount of dispersant and binder required to be consumed, that is, a large oil absorption value. When insufficient dispersant is added, the prepared anode slurry will form filter residue, which results in poor filtration.

[0215] It can be seen from the data in Table 1 above that, as shown in Examples 5, 6 and 9, a large amount of coating and a large number of surface functional groups are introduced, and the effect of inter-particle forces deteriorates the filtration and leads to a long filtration time.

[0216] It can be seen from the data in Table 1 above that, as shown in Examples 7 to 9, the higher the graphitization temperature, the greater the graphitization degree G.

[0217] It can be seen from the data in Tables 1 and 2 above that, as shown in Examples 3, 12 and 13, when the particle size range and weight fraction of needle coke are 5-15 parts for 10 μm-15 μm, 45-55 parts for 15 μm-25 μm, and 35-45 parts for 25 μm-30 μm, the comprehensive performance of the battery is better.

[0218] It can be seen from the data in Table 1 above that, as shown in Comparative Examples 1 to 3, the more the screening ratio of small particles is, the smaller the tap density TD is, and the oil absorption value becomes larger accordingly. In addition, there are many small particles and the TD value is low, which leads to an increase in the dispersant and binder required for consumption. When insufficient dispersant is added, the prepared anode slurry will form filter residue, which leads to worse filtration and longer filtration time. At the same time, the more the screening ratio of large particles is, the larger the tap density is, the smaller the oil absorption value is, the smaller the BET is, and the lower the energy density is.

[0219] From the data in Table 2 above, it can be seen that the shorter the filtration time, the less likely lithium precipitation will occur. This means that the shorter the filtration time, the more evenly the graphite particles are dispersed, no filter residue is formed, and there is sufficient graphite to provide sites for lithium, so lithium precipitation will not occur. However, if the filtration time is long, filter residue will appear on the surface, which proves that the local dispersion of the anode is poor and there may be a problem of local lithium precipitation.

[0220] It can be seen from Examples 1 to 4 in Table 2 that the DBP value is reduced, the electrode end surface is reduced, the filterability is improved, the energy density is reduced, and the fast charging and life are improved. It should be noted that the reduction in the end surface indicates that the channels for lithium ion embedding are reduced, the gram capacity is reduced, and the energy density is reduced.

[0221] It can be seen from Examples 3 and 9 to 11 that increasing the CMC content reduces the energy density, and a certain amount of increase can effectively improve the filterability and enhance the fast charging and cycle performance.

[0222] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A graphite, characterized in that: The graphite is prepared from needle coke, and the oil absorption value DBP of the graphite ranges from 45 to 54, in units of cm 3 / 100g, the tap density TD of the graphite is in the range of 1.0-1.1, in g / cm 3 The specific surface area of ​​the graphite is in the range of 1.45-1.6 (BET), in m 2 / g, the discharge capacity Cap of the graphite is in the range of 340-360, and the unit is mA·h / g.

2. The graphite according to claim 1, characterized in that The DBP of the graphite is in the range of 50-53, in cm 3 / 100g.

3. The graphite according to claim 1 or 2, characterized in that The graphitization degree G of the graphite is greater than 94%.

4. The graphite according to claim 1, characterized in that The Cap value of the graphite is in the range of 358-360, with the unit being mA·h / g.

5. The graphite according to any one of claims 1, 2 and 4, characterized in that The average particle size of the graphite is defined as Dv50, with the unit being μm, and the Cap, the Dv50 and the DBP satisfy the relationship: 15≤Cap / 360*(DBP-53)+Dv50≤18.

6. The graphite according to any one of claims 1, 2 and 4, characterized in that The Cap, the TD and the BET satisfy the relationship: 1.2≤Cap / 360*(TD-1.1)+BET≤1.

4.

7. A method for preparing graphite as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Providing needle coke, crushing, spheroidizing, coating, graphitizing and screening the needle coke to obtain graphite.

8. The method for preparing graphite according to claim 7, characterized in that: The process of crushing, spheroidizing, coating, graphitizing and screening the needle coke to obtain graphite includes the following steps: The needle coke is crushed, spheroidized, screened, batched, coated, graphitized and screened to obtain graphite.

9. The method for preparing graphite according to claim 8, characterized in that: In the step of batching the needle coke, the particle size range and weight fraction of the needle coke are as follows: 10μm-15μm5-15 copies; 15μm-25μm45-55 parts; 25μm-30μm is 35-45 copies.

10. The method for preparing graphite according to claim 9, characterized in that: The step of batching the needle coke comprises the following steps: Needle coke with a particle size of 10 μm-15 μm is added to needle coke with a particle size of 15 μm-25 μm and mixed. After mixing evenly, mixed powder A is obtained. Then, the mixed powder A is poured into needle coke with a particle size of 25 μm-30 μm and mixed. After mixing evenly, the batching is completed.

11. The method for preparing graphite according to claim 10, characterized in that: The step of pouring the mixed powder A into needle coke having a particle size of 25 μm-30 μm for mixing includes the following steps: First, 1 / 3-1 / 2 of the mixed powder A by weight is poured into needle coke with a particle size of 25 μm-30 μm for mixing, and after stirring evenly, the remaining mixed powder A is poured into needle coke with a particle size of 25 μm-30 μm for mixing.

12. The method for preparing graphite according to any one of claims 7 to 11, characterized in that: The step of coating the needle coke includes the following steps: The needle coke obtained in the previous step is mixed with the coating material to obtain a coated product, wherein the weight ratio of the needle coke to the coating material is 80:(3-22).

13. The method for preparing graphite according to claim 12, characterized in that: The coating material includes at least one of graphite, amorphous carbon, asphalt, metal and oxides thereof; And / or, the particle size of the coating material is 2 μm-4 μm.

14. The method for preparing graphite according to any one of claims 7 to 11 and 13, characterized in that: In the graphitization step, the following steps are included: The coated product obtained through the coating step is placed in a graphitization furnace, and in an inert atmosphere, the temperature is first raised to 1300° C.-1700° C. for high-temperature carbonization; The temperature is then raised to 2500°C-3200°C for graphitization, and after the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

15. The method for preparing graphite according to claim 14, characterized in that: The step of placing the coated product obtained through the coating step into a graphitization furnace and first heating it to 1300° C.-1700° C. for high-temperature carbonization includes the following steps: The coated product obtained through the coating step is placed in a graphitization furnace, and the temperature is first raised to 1300°C-1700°C at a heating rate of 50°C / min and kept at that temperature for 4 hours for high-temperature carbonization; And / or, the step of heating to 2500° C.-3200° C. for graphitization, and then slowly cooling the graphitization furnace to room temperature to obtain a graphitized product comprises the following steps: The temperature is raised to 2500-3200°C at a heating rate of 200°C / min, and the graphitization treatment is performed for 48h-72h. After the graphitization furnace is slowly cooled to room temperature, a graphitized product is obtained.

16. An anode slurry, characterized in that: The anode slurry comprises a dispersant and the graphite according to any one of claims 1 to 6.

17. The anode slurry according to claim 16, characterized in that The content of the dispersant accounts for 0.9%-1.5% of the solid matter content in the anode slurry.

18. The anode slurry according to claim 17, characterized in that The content of the dispersant accounts for 1.1%-1.3% of the solid matter content in the anode slurry.

19. The anode slurry according to any one of claims 16 to 18, characterized in that The discharge capacity of the graphite is defined as Cap, with a unit of mA·h / g, and the oil absorption value of the graphite is defined as DBP, with a unit of cm 3 / 100g, the content of the dispersant accounts for the solid matter content in the anode slurry is M, then the Cap, the DBP, and the M satisfy the relationship: 0.3%≤Cap / 360*(DBP-53) / 1000+M≤1.7%.

20. The anode slurry according to any one of claims 16 to 18, characterized in that The dispersant includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, aminoethyl cellulose and ethoxy cellulose.

21. A negative electrode plate, characterized in that: The negative electrode sheet includes a current collector and an anode slurry disposed on the current collector, wherein the anode slurry is the anode slurry according to any one of claims 16 to 20.

22. A battery, characterized in that: include: A negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet as claimed in claim 21.

23. An electrical equipment, characterized in that: The electric device comprises the battery as claimed in claim 22.

Citation Information

Patent Citations

  • Graphite particles for nonaqueous secondary battery and method for producing same, negative electrode and nonaqueous secondary battery

    CN103443977A